IMPLEMENTASI PROGRAM MOSLEM PERSONALITY INSURANCE DI MTS TANWIRUL QULUB - Imas Jihan Syah; Nur Iftitahul Husniyah (Institut Keislaman Abdullah Faqih (INKAFA) Gresik, 2020)
Abstrak: This article aims to explain about the implementation of the moslem personality insurance program owned by MTs Tanwirul Qulub Karanggeneng Lamongan, this program is a superior program that provides full assistance to students in the learning process in the school environment. This study uses a qualitative approach to the type of phenomenological research, informants of this study are principals, teachers and students, the technique of data retrieval is done by observation, interviews and documentation, while the data analysis is done by data reduction, data display and conclusions. The results of this study indicate that the Moslem Personality Insurance program at MTs Tanwirul Qulub is carried out by giving students habituation activities such as daily reports, morning khalaqoh, habituation of dhuha and dhuhur prayer together and home visit, from these activities students are able to develop values. character in himself as a good Muslim..Keywords: Moslem Personality Insurance